Self-consistent validation for machine learning electronic structure - Hu, G; Wei, G; Lou, Z; Torr, PHS; Ouyang, W; Zhong, H-s; Lin, C (2024)
Machine learning has emerged as a significant approach to efficiently tackle electronic structure problems. Despite its potential, there is less guarantee for the model to generalize to unseen data that hinders its application in real-world scenarios. To address this issue, a technique has been proposed to estimate the accuracy of the predictions. This method integrates machine learning with self-consistent field methods to achieve both low validation cost and interpret-ability. This, in turn, enables exploration of the model’s ability with active learning and instills confidence in its integration into real-world studies.